The inhibitory effect of tocilizumab on systemic bone loss and tendon inflammation in a juvenile Collagen-Induced arthritis rat model. (2nd November 2022) - Poutoglidou, Frideriki; Pourzitaki, Chryssa; Manthou, Maria Eleni; Samoladas, Efthimios; Saitis, Athanasios; Malliou, Foteini; Kouvelas, Dimitrios
ABSTRACT: Purpose of the study: Reduced Bone Mineral Density (BMD) is a prevalent comorbidity in Juvenile Idiopathic Arthritis (JIA). Enthesitis and other tendon abnormalities, such as tenosynovitis, tendinitis and tendon ruptures are, also, common extra-articular manifestations of the disease. The aim of the present study was to investigate the effect of tocilizumab, an antibody that binds the Interleukin-6 (IL-6) Receptor, on inflammation-related bone loss and tendon inflammation in an animal model of JIA. Materials and Methods: The Collagen-Induced Arthritis (CIA) model was induced in male rats followed by intraperitoneal administration of tocilizumab for 8 weeks. Methotrexate, the most widely used Disease-Modifying Antirheumatic Drug in the management of JIA, was, also, administered, either as a monotherapy or as an add-on therapy to tocilizumab. BMD was evaluated with Micro-Computed Tomography (Micro-CT) and histopathological examination. Tendon damage was, also, assessed histologically. Finally, two pro-inflammatory cytokines, Tumor Necrosis Factor-alpha (TNF-a) and Interleukin-23 (IL-23) were quantified in tendon tissues by ELISA analysis. Results: Tocilizumab-treated animals exhibited a significantly improved trabecular microarchitecture on micro-CT analysis and histological examination. Tendon morphology was also improved. Anti-IL-6 treatment led to a significant decrease in TNF-a and IL-23 expression in tendon tissue. Conclusions: The results of the present study provide evidence that tocilizumab reduces inflammation-related bone loss and suppresses tendon inflammation in a juvenile CIA rat model. These findings offer perspectives for the management of osteoporosis and enthesitis in JIA.